China's Dilemma : The Taiwan Issue - Sheng, Lijun (Book collections on Project MUSE., 2001)
This book is a study of the Taiwan issue after the Cold War. It focuses on the changes in Mainland China's Taiwan policy in the period between Lee Teng-hui's 1995 U.S. tour and his ""two states"" theory in 1999. It discusses why the tension across the Taiwan Strait flared up in 1995 and 1999, and how Mainland China handled, and is going to handle, its relations with Taiwan and the United States in the 21st century ...